Formation of SO, SO+, and S-2 by radiative association - Andreazza, C. M.; Marinho, E. P. (Univ Chicago Press, 2005)
Rate coefficients for radiative association of SO, SO+, and S-2 are estimated. For temperatures ranging from 300 to 14,000 K, the direct radiative association rate coefficients are found to vary with temperature from 1.73 x 10(-19) to 7.29 x 10(-19) cm(3) s(-1) and from 1.49 x 10(-21) to 3.70 x 10(-19) cm(3) s(-1) for S-2 and SO, respectively. The rate coefficients for formation through the inverse predissociation for S-2 are found to vary from 3.59 x 10(-18) to 1.44 x 10(-20) cm(3) s(-1). For SO+, the direct rate coefficient varies rapidly with temperature from 3.62 x 10(-27) cm(3) s(-1) at 2000 K to 2.34 x 10(-20) cm(3) s(-1) at 14,000 K. The direct radiative association rate coefficients increase with the increase in temperature, but the inverse predissociation rate coefficients decrease with the increase in temperature.
Keywords: astrochemistry; atomic data; atomic processes; ISM : molecules